Institutional factors of development of innovative performance in the Republic of Kazakhstan - Yessengeldina, A.S.; Kosdauletova, R.Ye.; Yardyakova, I.V. (Вестник Карагандинского университета, 2017)
This article focuses on the mechanism of state regulation of innovative sector. The authors noted that despite the increase in the number of innovative enterprises, the level of innovative performance is still very low and constitutes only 8.1 % of total output. Therefore, government policy ought to create relevant conditions for rising the scale of innovative performance of kazakhstani enterprises. It might also be significant to focus on measures aimed at creating an enabling environment that spurs innovation. According to the authors, every product manufactured incorporates the contribution of intellectual application of individual employees. Also, this article highlights that Kazakhstan producers lack the experience of bringing scientific research to the goods market and lacks highly qualified specialists in the field of project management. The authors further highlights the institutional framework necessary for innovative performance such as legal factors, material factors, financial factors, intellectual factors and state support. In the final section, a summary of the challenges facing the institutional framework supporting innovation in Kazakhstan is presented and some recommendations provided.
Қазақстан Республикасындағы инновациялық белсенділік дамуының институционалдық факторлары
Институциональные факторы развития инновационной активности в Республике Казахстан
Keywords: innovative activity; institutional factors; innovation; innovative enterprise